Goji berry (Lycium barbarum) has positive effects on the mucosa and colonic myoenteric innervation of obese rats - Samara Cristina Dossena; Isabela Ramos Mariano Furlan; Maria Montserrat Diaz Pedrosa; Rosângela Fernandes Garcia; Fernando Carlos de Sousa; Maria Raquel Marçal Natali (Journal of Functional Foods)
Goji berry (Lycium barbarum), characterized as a functional food, has been shown to be effective in the prevention and/or treatment of obesity. This study investigated the effects of Goji berry supplementation (250 mg/kg) on the intestine of male Wistar rats, from 70 to 130 days (group OGB) or 21 to 130 days (group OPR) of age, with obesity induced by simple carbohydrate-rich diet. The diet did not change the morphology or the thickness of the proximal colon wall but increased the proportion of small neurons in the myoenteric plexus. The use of the Goji berry extract had therapeutic effect on the obese animals (group OGB), decreasing body mass and mesenteric fat and increasing HDL cholesterol. As a preventive agent (group OPR) it reduced the body mass index, preserved the percentage of neutral mucins-producing goblet cells and increased the incidence of large neurons in the colonic myoenteric plexus. The use of the Goji berry extract is a promising alternative for the preservation and restoration of the intestinal structure and organization compromised by an obesogenic diet.